PEMBERIAN MAKANAN BERNUTRISI (TELUR) TERHADAP PERUBAHAN LUKA PASIEN KHITAN DI KLINIK DINAS KESEHATAN TENTARA (DKT 05.09.10) NGANJUK - Hutama, Fitra Handika; Utami, Rahayu Budi; Purwanto, Edi (LPPM STIKes SATRIA BHAKTI NGANJUK, 2022)
Introduction: This study aims to determine the changes in the wound of circumcised patients in the control group and the case group.The method in this study was to provide nutritious egg food to the control group and not to give egg nutritious food to the case group. This research was conducted at the Army Health Service Clinic (DKT 05.09.10) Nganjuk, involving 18 respondents. Based on this research, it can be seen that of the 9 respondents in the treatment group all experienced rapid wound healing, while 9 respondents in the case group all experienced slow wound changes. From the results of the Wilcoxon sign rank test statistic, it shows that value is 0.000 (0.05), so Ha is accepted and H0 is rejected. Coclusion Eggs are one of the food sources of animal protein that contain protein, fat, vitamins and minerals, so that eggs have good benefits in wound healing.